THE EFFECT OF WALK THROUGHT AUDIT (WTA) ON IMPROVING THE QUALITY OF HEALTH SERVICES IN THE FIRST LEVEL OF HEALTH FACILITIES - Dara Sa Fhounna; Maiza Duana (RADJA PUBLIKA, 2022)
This study aims to analyze how influential the Walk Through Audit (WTA) is on improving the quality of health services at the First Level Health Facility at the Johan Pahlawan Health Center, Meulaboh, Aceh Barat by using the direct interview method to participants of the National Health Insurance - Healthy Indonesia Card (JKN-KIS). ) which was assisted by a survey of JKN-KIS participants' satisfaction with the implementation of public services at the Johan Pahlawan Health Center, Meulaboh. This method focuses on theories and phenomena directly at the research site. The data used in this study is primary data. Primary data is data obtained by direct interaction with respondents. This aims to analyze the satisfaction of participants as users of health services at one of the first level health facilities (FKTP) in Meulaboh where through this WTA participants are directly involved in the function of supervising the fulfillment of the obligations of health facilities, and the results of the WTA will be one of the evaluation materials for services. first-level health facilities (FKTP) in order to improve the quality of health service delivery for JKN-KIS participants. The results of the research analysis show that the Walk Through Audit (WTA) has a positive and significant effect on improving the quality of health services at the First Level Health Facility at the Johan Pahlawan Health Center, Meulaboh City.